(untitled) (Південний архів (історичні науки), 2024)
The article attempts a historical analysis of individual pastoral letters and messages of the bishop of the Greek Catholic Church (hereinafter – GCC) in Galicia written and made public in the first half of the 20th century, namely: “Pastoral letter of Hryhori Khomyshyn, bishop of Stanislavivsk to the clergy of the Stanislavivsk diocese about Byzantium”; “Pastoral letter of Hryhoriy Khomyshyn, Bishop of Stanislavivskyi, to people of good will about the political situation of the Ukrainian people in the Polish state”; “An appeal to the venerable clergy of the Stanislaviv Diocese about the press as a very important weapon of the present age”; Letters on the topic: “Ukrainian problem”; “Pastoral letter of Grigory Khomyshyn, bishop of Stanislaviv to the clergy and faithful of the Stanislaviv eparchy about the storm of spiritual ruin”; Pastoral letter of Bishop Hryhoriy Khomyshyn of Stanislavivskyi to the clergy and faithful of the Stanislaviv Diocese about the Catholic Action and Pastoral Letter of Bishop Hryhori Khomyshyn of Stanislavivskyi to the clergy of the Stanislavivskyi Diocese “National or Revealed Faith or Collapse or Way of Creativity”. The purpose of the work is to carry out a historical analysis of the works and messages of the bishop of the Greek- Catholic Church Hryhori Khomyshyn, in particular, their ideological content, the context of creation, as well as determining their impact on the social and religious life of Ukrainian society. The research methodology is based on the principles: historical-biographical method and content analysis, comparative analysis, sociological method, source analysis, etc. The result of the research is that the problem of studying the literary heritage of this spiritual leader is to evaluate not only the religious, but also the social aspects of his activity. Hryhoriy Khomyshyn played a key role in strengthening the entire Ukrainian Greek Catholic Church, contributing to the formation of its identity against the background of the complex social and political conditions of that time and today. The scientific conclusion is that special attention is paid to the analysis of its impact on social processes in Galicia, in particular on the development of education, social justice and national revival. After all, Khomyshyn actively called for moral and spiritual improvement, which had a significant impact on the public consciousness of Ukrainians. His works are considered an important factor in the formation of national selfawareness and the support of Ukrainian statehood.